2013
DOI: 10.1002/star.201300026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on physicochemical properties of ensete and water caltrop with other root, tuber, and legume starches

Abstract: Structural and functional properties of starches from ensete pseudostems and water caltrop fruits were characterized and compared with other root and tuber (yam bean, taro, and cassava) and legume (chickpea and mungbean) starches. Taro and ensete starch granules were the smallest and largest, at respectively 2??m and 42??m average diameter. Amylose content varied from 7.91% in taro starch to 35.59% in chickpea starch with 19.20 and 20.85% in water caltrop and ensete starches. RVA analysis indicated that only w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Both the starch showed an A-type crystalline structure with characteristic reflection at about 15°, 23° 2θ and an unresolved doublet at 17° and 18° 2θ as observed in the diffractogram ( Figure 2 ). The diffractograms of most of the aroid starches are similar to this ( Lertphanich et al., 2013 ; Saikia and Konwar, 2012 ; Zeng et al., 2014 ).
Figure 2 XRD pattern of LT and AP starch granules.
…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Both the starch showed an A-type crystalline structure with characteristic reflection at about 15°, 23° 2θ and an unresolved doublet at 17° and 18° 2θ as observed in the diffractogram ( Figure 2 ). The diffractograms of most of the aroid starches are similar to this ( Lertphanich et al., 2013 ; Saikia and Konwar, 2012 ; Zeng et al., 2014 ).
Figure 2 XRD pattern of LT and AP starch granules.
…”
Section: Resultssupporting
confidence: 62%
“…B-type crystalline starches exhibit characteristic reflection at 5.6°, 15°, 17°, 22° and 23° and C-type crystalline starches exhibit both A and B diffractograms and will be further classified into CA-, CB-, and CC-type based on their resemblance to A- and B-type or between the two types, respectively. Earlier studies suggest that starch with low amylose content shows an A-type XRD pattern ( Lertphanich et al., 2013 ; Wani et al., 2015 ; Riley et al., 2004 ; Padmanabhan and Lonsane, 1992 ). This is further corroborated by this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During oven heating, in the lower protein content samples water was probably absorbed by the starch granules to gelatinise, while the high protein samples showed more dehydration. Furthermore, with temperature increasing over the gelatinisation temperature, water continues to be absorbed by starch, leading to disorganisation of the crystalline structure and more solid-like texture, affecting meltability, and this is probably due to the high levels of amylose in chickpea starch ( Lertphanich et al, 2013 ; Zhang et al, 2016 ). Poor melting characteristics were previously observed for commercial plant-based cheese products ( Grasso et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Its fruits and husks have a rich content consisting of starch, dietary fibre, essential amino acids and some types of phenols and minerals. Previous studies have shown that TN leaves, fruits, husks, flowers and roots have 19.5% amylose (Lertphanich et al, 2013), 1.9 mg/g phosphorus (Akao et al, 2013;Zhu, 2016), fatty acids such asnervonicacid (63.5%), α-linolenic acid (6.4%), palmitolenic acid (6.4%), linoleic acid (6.3%) (Mukherjee et al, 2010;Zhu, 2016), phenols such as caffeic acid, chlorogenic acid, ferrulic acid and 3-Omethylgallic acid (Stoicescu et al, 2012;Zhu, 2016), flavonoids such as quercetin and kaempferol (Niranjan et al, 2013;Zhu, 2016). The majority of fatty acids (69.3%) in the TN content form unsaturated fatty acids (Mukherjee et al, 2010).…”
Section: Introductionmentioning
confidence: 97%